Unilateral contact applications using FEM software - Stavroulaki, Maria E.; Stavroulakis, Georgios E. (Zielona Góra: Uniwersytet Zielonogórski)
Nonsmooth analysis, inequality constrained optimization and variational inequalities are involved in the modelling of unilateral contact problems. The corresponding theoretical and algorithmic tools, which are part of the area known as nonsmooth mechanics, are by no means classical.
Keywords: nonsmooth analysis; constrained optimization; contact problems